67.9k views
1 vote
Suppose that the functions f and g are defined for all real numbers x as follows.

f(x) = x - 5, g(x) = 2(x) + 6
Write the expressions for (f*g)(x) and (f-g)(x)..

1 Answer

5 votes

Answer:


(f*g)(x)=2x^(2)-4x-30\\


(f-g)(x)=-(x+11)\\

Explanation:

the expression (f*g)(x) can be expanded as follows


(f*g)(x)=f(x)*g(x)\\

since
f(x)=x-5,g(x)=2x+6

Hence


(f*g)(x)=f(x)*g(x)\\(f*g)(x)=(x-5)*(2x+6)\\(f*g)(x)=2x^(2)+6x-10x-30\\(f*g)(x)=2x^(2)-4x-30\\

also the expansion for (f-g)(x) is express as


(f-g)(x)=f(x)-g(x)\\

also since


f(x)=x-5,g(x)=2x+6 then when we substitute values, we have


(f-g)(x)=(x-5)-(2x+6)\\(f-g)(x)=x-5-2x-6\\(f-g)(x)=-x-11\\(f-g)(x)=-(x+11)\\

For this type of operation kindly note the below expansions


(f*g)(x)=f(x)*g(x)\\


(f-g)(x)=f(x)-g(x)\\


(f+g)(x)=f(x)+g(x)\\


(f/g)(x)=f(x)/g(x)\\

User Bewildered
by
6.1k points